Association of the microbiological profile with cytological changes in quilombolas women at the basic health units - Aragão, Francisca Bruna Arruda; dos Santos, Gerusinete Rodrigues Bastos; de Mello Lobão, Walder Jansen; de Oliveira, Anderson Pereira; Monteiro, Silvio Gomes; Santos, Lana Meireles; Reis, Andréa Dias [UNESP]; Neto, Marcelino Santos; Batista, José Eduardo (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
Aim: Analyzing the microbiological profile and associate it with cytological alterations in quilombola women with cervical-vaginal lesions. Material and Methods: This was a 5-month cross-sectional study based on 154 quilombola women, in the 13 to 74 years age group, recorded in the Sistema Único de Saúde (SUS) with cervical-vaginal lesions. Results: Women aged 45 years and older (43.5%) had the most Pap smears, followed by women in the 31 to 45 years (31,2%) and ≤30 years old (25,3%). The most common infection in women of ≤30 years old was Gardnerella (35,8%) and in the 31 to 45 years group was Lactobacillus (47,9%). The overall prevalence of cytological abnormalities was 7.8%, with higher frequency in the 31 to 45 years group. Conclusion: The microbiological profile in the quilombola women with bacterial vaginosis had the highest cellular atypias prevalence and no statistically significant association was found between the age range and cervical-vaginal changes, as well as the microbiota had no association with cytological abnormalities.
Associação do perfil microbiológico com alterações citológicas em mulheres quilombolas atendidas nas unidades básicas de saúde
Keywords: Cervix Uteri; Papanicolaou Test; Prevalence; Vaginal Smears